Nedenleri ve Sonuçları ile Çocuk İşçiliği - Ocakçı, Ayşe Ferda; Subaşı, Damla Özçevik; Yüceol, Hüseyin Mualla; Akın, Levent; Dinç Ütükler, İstemi Ceysu; Karadeniz , Meltem; Çatıker, Aslıhan; Tekin Yılmaz, Tülay; Tatoğlu, Nilüfer; Kuzlu Ayyıldız, Tülay; Bozdağ, Fatma; Oruç, Deniz; et al. (2024)
-